Whole‐genome sequencing of hMPXV1 in five Italian cases confirms the occurrence of the predominant epidemic lineage. Issue 2 (18th January 2023) - Forni, Diego; Moltrasio, Chiara; Sironi, Manuela; Mozzi, Alessandra; Quattri, Eleonora; Venegoni, Luigia; Zamprogno, Marzia; Citterio, Andrea; Clerici, Mario; Marzano, Angelo Valerio; Cagliani, Rachele
Abstract: The ongoing outbreak of monkeypox virus (hMPXV1) is the largest recorded in historically nonendemic countries. Genomic surveillance has emerged as a pivotal tool to track the spread and monitor the evolution of viral pathogens. Therefore, to assess the genetic diversity of circulating hMPXV1 in northern Italy in June to July 2022, we sequenced and analyzed five complete genomes of viruses sampled from patients presenting with a typical course of hMPXV1 infection. Phylogenetic analysis confirmed that all five genomes belong to the predominant epidemic lineage (B.1). Inspection of genetic changes and comparison with the reference sequence showed the presence of 12 nucleotide substitutions. Seven are nonsynonymous mutations leading to amino acid changes in six proteins belonging to different functional classes. Moreover, 11 of these 12 nucleotide mutations involve GA>AA or TC>TT replacements, suggesting that host APOBEC3 enzymes are responsible for the generation of substitutions in circulating viruses. Finally, metagenomic analysis evidenced bacterial superinfection ( Streptococcus pyogenes ) in one patient. Through this study, we contributed to expand the number of complete genomes of viruses circulating in Italy and characterize them as belonging to the predominant outbreak lineage.